Turpin and Tomkins' British government and the constitution : text and materials - Young, Alison L.; Turpin, Colin; Tomkins, Adam (Cambridge : Cambridge University Press, 2021)
A lot has happened to the UK Constitution in the last seven years. We've witnessed the UK's exit from the EU, further devolution to Scotland and Wales, a number of prominent cases by the Supreme Court, two early parliamentary general elections, major governmental defeats and two Prime Ministerial resignations. Alison Young has built on the text of Colin Turpin and Adam Tomkins' earlier edition, keeping their unique historical and contextual approach, whilst bringing the material up to date with more contemporary examples, including references to Brexit, the recent prorogation and Brexit case law, and the Covid-19 pandemic. The book continues to include substantial extracts from parliamentary and other political sources as well as from legislation and case law. It also provides a full yet accessible account of the British constitution at the culmination of a series of dramatic events, on the threshold of possible further constitutional reform.
Title from publisher's bibliographic system (viewed on 27 Apr 2021).
Keywords: elektronické knihy; electronic books; Constitutional law -- Great Britain; Constitutional law -- Great Britain -- Cases